Experimental and numerical study on casing wear in highly deviated drilling for oil and gas. (June 2016) - Yu, Hao; Lian, Zhanghua; Lin, Tiejun; Liu, Yonghui; Xu, Xiaofeng
Aimed at studying the casing wear in the highly deviated well drilling, the experimental study on the casing wear was carried out in the first place. According to the test data and the linear wear model based on the energy dissipation proposed by White and Dawson, the tool joint–casing wear coefficient was obtained. The finite element model for casing wear mechanism research was established using ABAQUS. The nodal movement of the contact surface was employed to simulate the evolution of the wear depth, exploiting the Umeshmotion user subroutine. In addition, the time-dependent geometry of the contact surfaces between the tool joint and casing was being updated continuously. Consequently, the contact area and contact pressure were changed continuously during the casing wear process, which gives a more realistic simulation. Based on the shapes of worn casing, the numerical simulation research was carried out to determine the remaining collapse strength. Then the change curve of the maximum casing wear depth with time was obtained. Besides, the relationship between the maximum wear depth and remaining collapse strength was established to predict the maximum wear depth and the remaining strength of the casing after a period of accumulative wear, providing a theoretical basis for the safety assessment of worn casing.